Influence of ageing time on yield and texture of marinated chicken breast cooked using a continuous process - Sartori,Tais Colpo (2014)
The objective of this study was to evaluate the influence of different ageing times before deboning (deboning time) and ageing times after deboning (holding time) on the quality (sensory attributes and texture) and cooking loss of chicken breast marinated, cooked and frozen using a continuous process.The following3² experimental design was used (3 deboning times: zero, 6 and 12 hours; and 3 holding times: zero, 12 and 24 hours). Brine absorption, chicken breast pH and cooking loss were evaluated, a sensory analysis was carried out and the shear force was determined. The deboning and holding times did not significantly influence brine absorption and pH, but did significantly influence cooking loss, where the lowest value obtained was a mean of 19.72% for deboning times of 6 or 12 hours and a holding time of 24 hours. A deboning time of 6 hours was sufficient to improve tenderness as measured by a sensory analysis and shear force determination.